Engaging Same-Day Peer Ambassadors to Increase Coronavirus Disease 2019 Vaccination Among People Experiencing Unsheltered Homelessness in Los Angeles County: A Hybrid Feasibility-Evaluation Study . (7th October 2022) - Shover, Chelsea L; Rosen, Allison; Mata, José; Robie, Brooke; Alvarado, Julissa; Frederes, Ashley; Romero, Ruby; Beltran, Jacqueline; Bratcher, Anna; Chang, Alicia H; Choi, Kristen R; Garcia, Candelaria; et al.
Abstract: Background: This study aimed to evaluate the feasibility and acceptability of engaging unhoused peer ambassadors (PAs) in coronavirus disease 2019 (COVID-19) vaccination efforts to reach people experiencing unsheltered homelessness in Los Angeles County. Methods: From August to December 2021, vaccinated PAs aged ≥18 years who could provide informed consent were recruited during vaccination events for same-day participation. Events were held at encampments, service providers (eg, housing agencies, food lines, and mobile showers), and roving locations around Los Angeles. PAs were asked to join outreach alongside community health workers and shared their experience getting vaccinated, receiving a 25 gift card for each hour they participated. Postevent surveys evaluated how many PAs enrolled and how long they participated. In October 2021, we added a preliminary effectiveness evaluation of how many additional vaccinations were attributable to PAs. Staff who enrolled the PAs estimated the number of additional people vaccinated because of talking with the PA. Results: A total of 117 PAs were enrolled at 103 events, participating for an average of 2 hours. At events with the effectiveness evaluation, 197 additional people were vaccinated over 167 PA hours (21.19 gift card cost per additional person vaccinated), accounting for >25% of all vaccines given at these events. Discussion: Recruiting same-day unhoused PAs is a feasible, acceptable, and preliminarily effective technique to increase COVID-19 vaccination in unsheltered settings. The findings can inform delivery of other health services for people experiencing homelessness.